ANALISIS PENGETAHUAN KEWIRAUSAHAAN DAN SIKAP MANDIRI TERHADAP MINAT BERWIRAUSAHA ALUMNI PONDOK MODERN DARUSSALAM GONTOR - Sa’diah, Zulfatus; Sukaithin, Oma (Politeknik Negeri Lhokseumawe, 2024)
Abstract: Currently, Indonesia's economic development is considered lacking because there is little public interest in starting a business. As evidenced by comparative data on the entrepreneurial population in 7 ASEAN countries, Indonesia is in the second lowest level after Myanmar. For this reason, creating active and creative entrepreneurs needs to start from the level of interest in entrepreneurship. Entrepreneur-based school alumni have added trustworthiness to increase the criteria for people who are interested in entrepreneurship. This can also be obtained from Islamic boarding school alumni who provide entrepreneurial knowledge and various entrepreneurial practices. Apart from entrepreneurial knowledge, another thing that can play a strong role in influencing the desire to become an entrepreneur is an independent attitude. So, the aim of this research is to determine the influence of entrepreneurial knowledge and independent attitudes on the entrepreneurial interest of Pondok Modern Darussalam Gontor alumni. This research uses a quantitative approach. The sampling technique used was purposive sampling, with a total sample of 130 alumni selected. The data processing and analysis technique uses Variance Based Structural Equation Modeling, the Partial Least Square (PLS) method with the help of SmartPLS 3.0. The results of this research say that the test results between entrepreneurial knowledge and entrepreneurial interest have a path coefficient value of 0.386, which means the number is close to +1, thus illustrating the relationship produced by the exogenous variable (entrepreneurial knowledge) and the endogenous variable (entrepreneurial interest) is a positive relationship. And it has a T-Statistic value of 2.221 (1.96) so it is said to be significant for interest in entrepreneurship. And the test results between independent attitude and interest in entrepreneurship have a path coefficient value of 0.145, which means the number is close to +1 so that it illustrates the relationship produced by the exogenous variable (independent attitude) with the endogenous variable (interest in entrepreneurship) is a positive relationship. However, it has a T-Statistic value of only 1.415 (1.96) so it is said that it is not significant for interest in entrepreneurshipKeywords: Entrepreneurial Knowledge, Independent Attitudes, and Entrepreneurial Interest